New EU projects delivering human microbiome applications - Dirk Hadrich (Future Science OA)
Over recent years, the number of studies and projects showing correlations between the human microbiome and diseases has increased enormously. The potential of the human microbiome for healthcare is big. However, many confounders have been discovered and the relevant disease mechanisms and the causalities of these diseases still require more efforts and better understanding. The EU called for project proposals exploiting the application potential of human microbiome research and finally decided to fund the three top excellent new H2020 projects ONCOBIOME, MICROB-PREDICT and GEMMA. They get a total EU funding of €44 M and started in January 2019 with the aim to deliver high impact through validated clinical tools that are helpful for end-users.